School Climate and School Effectiveness: Summary of Teacher, Student and Parent Attitudes in One Rural Community - Robert W. Maloy; Clement A. Seldin (Journal of Research in Rural Education, 1983)
This paper presentsa comparison of how teachers, students, and parents perceivethe climateof the secondary schools in Greenfield, Massachusetts. The study is a product of a four-year collaboration (1977-1981)between the Greenfield, Massachusetts, Public Schools, the Massachusetts Department of Education, and the University of Massachusetts School of Education. Examining school climate, the paper assesses the extent to which teachers, students, and parents vieweight selectedvalue statements about the purposes of school differently. Agreement between teachers, students, and parents on the purposes of school suggests the presence of common beliefs about school and supports a "school climate of collaboration." Disagreement, by contrast, indicates the presence of alternate, potentially conflicting, beliefs and produces a "school climate of contention." The survey data suggested that the Greenfield students feel more positively than their parents or teachers about the ability of school to prepare them for later life. According to the students, whatever purposes parents and teachers think should be emphasized are being emphasized. By contrast, parents and teachers identify considerable differences between what they wish would be emphasized and what they thought was being emphasized. Based on these results, the paper concludes that the differences in teacher, parent, and student perceptions about the purposes of school will have important implications for the question of school effectiveness in Greenfield